2011
DOI: 10.1128/jb.00948-10
|View full text |Cite
|
Sign up to set email alerts
|

XerCD-Mediated Site-Specific Recombination Leads to Loss of the 57-Kilobase Gonococcal Genetic Island

Abstract: Most strains of Neisseria gonorrhoeae carry the 57-kb gonococcal genetic island (GGI), as do a few strains of Neisseria meningitidis. The GGI is inserted into the chromosome at the dif site (difA) and is flanked by a partial repeat of the dif site (difB). Since dif is a sequence recognized by the site-specific recombinases XerC and XerD and the GGI shows evidence of horizontal acquisition, we hypothesized that the GGI may be acquired or lost by XerCD-mediated site-specific recombination. We show that while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 41 publications
0
62
0
Order By: Relevance
“…IMEXs are nevertheless rarely excised and lost. The GGI is present in 80% of N. gonorrheae strains and the excised form is barely detected (8,9). We have shown here that the integrated form of the GGI is flanked by two active Xer sites.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…IMEXs are nevertheless rarely excised and lost. The GGI is present in 80% of N. gonorrheae strains and the excised form is barely detected (8,9). We have shown here that the integrated form of the GGI is flanked by two active Xer sites.…”
Section: Discussionmentioning
confidence: 68%
“…Comparison of N. gonorrheae strains harboring or lacking the GGI, together with functional data, indicates that the GGI integrates by XerCD-dependent recombination (9). The nonreplicative excised circular form of the GGI can be detected and the GGI can also be lost, showing that excision occurs, although at low frequencies (9). Although the GGI…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The secreted DNA also acts in the initiation of biofilm development (5). The genes for the gonococcal T4SS are encoded on the gonococcal genetic island (GGI), a 57-kb genetic island that was likely horizontally acquired and is inserted in the chromosome near the replication terminus (1,2,6). T4SSs are a diverse family of transmembrane complexes that include both conjugation systems (such as F plasmid and the IncN plasmid pKM101) and effector translocator systems that deliver proteins or DNAprotein complexes directly into host cells (such as the well-studied VirB/D T4SS in Agrobacterium tumefaciens) (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…It was previously suggested that GGI initially harbored true neisserial dif sites and that their stabilization resulted from mutations that occurred after their integration (5). Many different types of mutations, including mutations in the central region of the dif sites and mutations abolishing the binding of the recombinases to them, could impede Xer recombination.…”
mentioning
confidence: 99%